A systematic approach to the effective strategy and plan of stakeholders for safety improvement during decommissioning of nuclear facilities. (August 2021) - Jeong, KwanSeong; Choi, ManSoo; Kim, Alexandr; Lee, JungJun; Lee, ByungSik
Highlights: The important factors of stakeholders for safety improvement during decommissioning. Stakeholder engagement throughout the life cycle of nuclear facilities. The engagement process and methods of stakeholders. The critical success factors for effective stakeholder engagement. Abstract: This paper is intended to identify a large spectrum of possible stakeholders and important factors for safety improvement during decommissioning of nuclear facilities. The relevant stakeholders of decommissioning have been analyzed. The engagement process and methods of stakeholders have been reviewed. The critical success factors for effective stakeholder engagement during decommissioning of nuclear facilities have been discussed.